2017
DOI: 10.1111/irj.12196
|View full text |Cite
|
Sign up to set email alerts
|

Work, employment and engagement conditions in a female‐dominated public service occupation after restructuring/outsourcing

Abstract: Most research on the phenomenon of public service restructuring/outsourcing focuses on lower skilled work in peripheral activities and typically provides an overview of effects on work, employment and employment relations. Through an in‐depth case study of probation, the intention of this article is to explore professional worker experiences of the restructuring/outsourcing of a core public service activity where the workforce is female dominated. The article highlights three dimensions of job quality that all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…A small number of UK and US studies map what has become referred to as the ‘feminisation’ of probation in the late 20th century, a term used to describe significant increases in the number of females entering the profession, including across senior roles, and the impacts of these shifts on probation’s developing identity, standing, and practice (Annison, 2007; Kirton and Guillaume, 2018; Mawby and Worrall, 2013; Zettler, 2019). Annual data produced by the Scottish Social Services Council indicate similar shifts in Scotland.…”
Section: Review Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…A small number of UK and US studies map what has become referred to as the ‘feminisation’ of probation in the late 20th century, a term used to describe significant increases in the number of females entering the profession, including across senior roles, and the impacts of these shifts on probation’s developing identity, standing, and practice (Annison, 2007; Kirton and Guillaume, 2018; Mawby and Worrall, 2013; Zettler, 2019). Annual data produced by the Scottish Social Services Council indicate similar shifts in Scotland.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…For example, Mawby and Worrall (2013) reported that the increasingly ‘female voice’ of probation may have resulted in its absence at more senior male-dominated levels of the criminal justice system. Further, Kirton and Guillaume (2018) speculate that the recent reorganisation and outsourcing of the probation service in England and Wales has served to devalue probation work, primarily now women’s work, somewhat deprofessionaling it.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…7 Similarly, calls to review the current contractual requirements in order to provide increased funding to greater incentivise the CRCs (CJJI, 2016: 9) do not go far enough in our opinion and only serve to further embed the link between punishment, social control, and corporate profits (Gottschalk, 2014). There are indications that there has been a reduction in performance and detrimental impact on staff morale, within both the CRCs and NPS, following the dissolution of the former Probation Trusts (HMI Probation, 2014, 2015a, 2015b, 2016; Kirton and Guillaume, 2015). Extending the scope of private enterprise to address problems created by the break-up of the public probation service therefore appears counter-intuitive to say the least.…”
Section: Conclusion: Too Little Too Late?mentioning
confidence: 99%
“…Previous literature regarding TR outlined emerging cultural differences between CRC and NPS practitioners, that contributed towards a perception that the CRC inhabited a second class status (see e.g. Clare, 2015; Kirton and Guillaume, 2015). Findings from the case study CRC posit that the fragmentation and legitimacy concerns position TSO practitioners as a perceived ‘third class’ of offender management, operating at a level below those of CRC staff.…”
Section: Resultsmentioning
confidence: 99%